Recent studies on Polyphenols: Extraction technologies and prospects - Stefanos Leontopoulos; Vasilios Chatzitheodorou; Prodromos Skenderidis (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Polyphenols constitute a group of the most important bioactive compounds widely represented naturally in many plant species. Fresh plant tissues, plant residues, and agro-wastes contain consequent amounts of polyphenolic compounds. In recent years, there is a developing interest in utilizing these bioactive compounds for nutraceutical and pharmaceutical applications due to their beneficial effects on human health and their potential in improving the quality of food. However, their effectiveness is depending on many factors such as the extraction technique, the plant tissue, and species origin, environmental factors, the solvent used for the extraction, etc. The purpose of this critical review is to address and give an insight into the latest review and research articles regarding extraction methods and highlights the prospects of bioactive compounds found in several plant tissues.